Orexin-A in Patients With Lewy Body Disease: A Systematic Review and Meta-Analysis - Gan, Jinghuan; Chen, Zhichao; Han, Jiuyan; Ma, Lingyun; Liu, Shuai; Wang, Xiao-Dan; Ji, Yong (Frontiers in Endocrinology, 2021)
Abnormal orexin-A levels in cerebrospinal fluid (CSF) have been identified in Alzheimer’s disease (AD) and other neurodegenerative diseases. However, few studies have focused on Lewy body disease (LBD), and often with debatable outcomes. Thus, we performed this systematic review and meta-analysis to investigate orexin-A levels in LBD by incorporating data from different studies. We gathered studies comparing orexin-A levels in patients with LBD and controls (including healthy controls and other dementia subtypes). In the initial search, 117 relevant articles were identified. After a selection process, seven studies, conducted in Japan, USA, Spain, Switzerland, France, Italy, and the Netherlands, were chosen. In total, 179 patients with LBD and 253 controls were included. Patients with LBD had significantly lower mean orexin-A CSF levels when compared with patients with AD (standard mean difference [SMD]: −0.35, 95% confidence interval (CI): −0.70 to −0.00, Z=1.96 and P=0.05), whereas mean orexin-A levels were significantly higher when compared with patients with frontotemporal lobar degeneration (FTLD) (SMD: 0.61, 95% CI: 0.23 to 0.99, Z=3.12 and P=0.002). Orexin-A CSF levels in LBD patients were approximately equal to levels in healthy elderly individuals, whereas they were significantly decreased in LBD patients with excessive daytime sleepiness (EDS) (SMD: -0.15, 95% CI: -0.59 to 0.29, Z=0.67 and P=0.50). We showed that orexin-A levels in patients with LBD were not very different from normal elderly individuals, whereas were lower than AD and higher than FTLD patients. The influence of hypersomnia on orexin-A levels should be carefully interpreted.